Pengaruh Kualitas Pelayanan dan Fasilitas Terhadap Kepuasan Konsumen di Four Seasons Resort Bali at Jimbaran Bay Kabupaten Badung - I Kadek Adiguna Pranata; Ida Ayu Anggreni Suryaningsih; I Wayan Kartimin (Jurnal Mosaik Hospitaliti, 2026)
The rapid development of Bali's tourism sector has intensified competition among hospitality businesses, encouraging hotels to continuously enhance both their service standards and physical amenities to achieve higher levels of guest satisfaction. This research aims to investigate the extent to which service quality and hotel facilities affect customer satisfaction at Four Seasons Resort Bali at Jimbaran Bay, located in Badung Regency. The study adopted a quantitative research method using a descriptive design. Primary data were obtained from 80 guests who had previously stayed at the resort through an online questionnaire created with Google Forms. The responses were processed and examined using multiple linear regression analysis with SPSS version 25. The empirical results indicate that service quality exerts a positive and statistically significant influence on customer satisfaction. Similarly, the availability and condition of hotel facilities are also found to have a significant positive impact on guests' satisfaction levels. The simultaneous regression test further demonstrates that both variables collectively contribute to explaining variations in customer satisfaction. These findings suggest that delivering reliable services while maintaining well-equipped and comfortable facilities is fundamental to creating positive guest experiences. Therefore, the study concludes that customer satisfaction at Four Seasons Resort Bali at Jimbaran Bay is largely determined by the combined effect of service quality and hotel facilities, highlighting the importance of continuously improving both aspects to sustain guest loyalty and remain competitive within Bali's hospitality market.